Literature Analysis on the Effectiveness of Referral Systems in Improving Access to Health Services - Oryza Sativa H Sihotang; Putri Adinda Ramadhani; Hutagalung; Nur Indah Rahma Dilla; Zahra Andini; Nadhilah hasibuan; Dewi Agustina (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
In Indonesia, the healthcare referral system has undergone a major shift from a conventional model to an integrated electronic system. Seven scientific articles published between 2020 and 2024 are the subject of this study. The purpose of this study is to evaluate the effectiveness of the electronic referral system in improving access to health services. The research results show that the implementation of electronic referral systems such as SISRUTE in the JKN BPJS Kesehatan program has improved the referral process and reduced patient waiting times. However, challenges such as limited technology infrastructure, labor shortages, the complexity of system interfaces, and fear of change still exist. Information quality, ease of use, management support, and data integration greatly influence system performance. The electronic referral system is essential for reducing maternal and infant mortality rates in delivery and maternal care services. Therefore, several important recommendations for the development of a referral system in Indonesia are continuous evaluation, increased employee capacity, strengthening regulations, and integration of health information systems.